PKM EDUKASI KONSEP PEMASARAN PRODUK KEPADA PENGURUS YAYASAN BINA MUJTAMA’ - Ridwan Usman; Elfitria Wiratmani; Muhammad Habiburrahman (Jurnal Abdimas Bina Bangsa, 2023)
Today's business world has entered a globalization process that is increasingly open and requires marketers or companies to always follow it with full awareness to further strengthen the implementation of professional and modern management for each company involved in the open market so that the company can maintain its existence and develop. Therefore, in this era of openness, competition among business actors will of course be increasingly sharp, while the competition in the marketing arena will also be increasingly fierce. Marketing is an activity of conveying the needs of individual life. This relates to identifying what customers need or want, then planning and developing products and services to satisfy them. needs and how to determine the right price, promotion, distribution channel. The goal of a business is to create customers emphasizing two aspects, namely identifying needs. consumers and manage the business to meet consumer needs. The problems faced by the Management Partners of the Bina Mujtama Foundation are, firstly, the Product Marketing System has not been properly implemented by the Management of the Bina Mujtama Foundation. Second, the lack of understanding of the Product Marketing Concept. Therefore, there is a need for training to increase the knowledge and skills of the foundation's management regarding the Product Marketing Concept. So the purpose of this Community Service is to provide an understanding of Product Marketing Concept Education